Resin composition, thermally conductive resin sheet, laminated heat dissipation sheet, heat dissipation circuit board, and power semiconductor device

JP7643129B2Active Publication Date: 2025-03-11MITSUBISHI CHEM CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021051363
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-03-25
Publication Date
2025-03-11
Estimated Expiration
2041-03-25

AI Technical Summary

Benefits of technology

【0015】 本発明の樹脂組成物から得られる熱伝導性樹脂シートは、吸湿リフロー耐性に優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643129000003
    Figure 0007643129000003
  • Figure 0007643129000004
    Figure 0007643129000004
  • Figure 0007643129000005
    Figure 0007643129000005
Patent Text Reader

Abstract

To provide a thermally conductive resin sheet having excellent moisture absorption reflow resistance.SOLUTION: There is provided a resin composition comprising a thermoplastic resin and a thermally conductive filler, wherein the tensile storage modulus (E'(200)) at 200°C of the thermoplastic resin is 8.0×107 or more and 1.0×1010 Pa or less and the mass increasing rate at 85°C and 85% RH of the resin composition is 0.15% or less. Further, there is provided a resin composition comprising a thermoplastic resin and a thermally conductive filler, wherein the tensile storage modulus (E'(300)) at 300°C of the thermoplastic resin is 4.0×107 Pa or more and 1.0×109 Pa or less and the mass increasing rate at 85°C and 85% RH of the resin composition is 0.15% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a thermally conductive resin sheet made of the resin composition, a laminated heat dissipation sheet obtained by laminating a metal plate material onto the thermally conductive resin sheet, and a heat dissipation circuit board further comprising a conductive circuit laminated thereon. [Background technology]

[0002] In recent years, power semiconductor devices used in various fields such as railways, automobiles, industry, and general home appliances are being shifted from conventional Si power semiconductors to power semiconductors using SiC, AlN, GaN, etc. in order to achieve further miniaturization, cost reduction, and efficiency improvement. Power semiconductor devices are generally used as power semiconductor modules in which a plurality of semiconductor devices are arranged on a common heat sink and packaged.

[0003] Various issues have been pointed out for the practical application of such power semiconductor devices, one of which is the issue of heat generation from the devices. Although power semiconductor devices can achieve high output and high density by operating at high temperatures, there are concerns that the heat generated by device switching will reduce the reliability of the power semiconductor devices.

[0004] In recent years, particularly in the electrical and electronics fields, heat generation due to the increasing density of integrated circuits has become a major problem, and how to dissipate heat has become an urgent issue. One method to solve this problem is to use highly thermally conductive ceramic substrates such as alumina substrates and aluminum nitride substrates as heat dissipation substrates on which power semiconductor devices are mounted. However, ceramic substrates have disadvantages such as being easily cracked by impact, and being difficult to make thin and compact.

[0005] Therefore, a heat dissipation sheet using a thermosetting resin such as an epoxy resin and an inorganic filler has been proposed. For example, Patent Document 1 proposes a heat dissipation resin sheet containing an epoxy resin having a Tg of 60° C. or less and boron nitride, in which the boron nitride content is 30 volume % or more and 60 volume % or less.

[0006] Patent Document 2 proposes a film for metal substrates, which is characterized by containing an inorganic filler having an average major axis of 1 to 50 μm in a polyether ketone resin.

[0007] Patent Document 3 proposes a heat-resistant and heat-conductive packing in which polyether ether ketone (PEEK) is filled with a heat-conductive filler.

[0008] Furthermore, Patent Document 4 proposes a polymer composition in which at least one oxide having an electronegativity in a specific range and at least one nitride having an electronegativity in a specific range are added to a semicrystalline polymer.

[0009] On the other hand, Patent Document 5 proposes an inorganic-organic composite material having a structure in which boron nitride particles serving as a highly thermally conductive filler are dispersed in a resin serving as a matrix, the boron nitride particles being dispersed in the resin in the state of "exfoliated flat particles" produced through a process of interlaminar delamination of secondary particles, which are laminates of primary particles. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2017-036415 A [Patent Document 2] Japanese Patent Application Publication No. 03-020354 [Patent Document 3] Japanese Patent Application Publication No. 07-157569 [Patent Document 4] Special Publication No. 2008-524362 [Patent Document 5] JP 2012-255055 A Summary of the Invention [Problem to be solved by the invention]

[0011] The reflow process is one of the processes for assembling power semiconductor modules. In this reflow process, the temperature of the components is raised rapidly to melt the solder and join the metal components together. In recent years, the operating temperature of power semiconductor devices has increased with the increase in output and density, so the solder used in the reflow process is also required to be heat resistant, and it has become common to use high-temperature solder that requires a reflow temperature of 290°C. Therefore, in the reflow process, the process of raising the temperature to around 290°C at which the high-temperature solder flows and then cooling it is repeated. Moreover, when mounting a power semiconductor device on a module, heating and cooling are also repeated in a similar manner.

[0012] When a circuit board having a metal plate or the like bonded to a conventional heat dissipation resin sheet is used, repeated temperature changes during the reflow process or the like cause thermal expansion and contraction, and the difference in the thermal expansion coefficients between the resin and the metal plate can cause interfacial peeling between the heat dissipation resin sheet and the metal plate, resulting in a decrease in the performance of the power semiconductor module. In addition, there have been cases where the components absorb moisture during storage prior to the reflow process, which significantly accelerates deterioration of the components during the reflow process, further deteriorating the performance of the power semiconductor module.

[0013] Therefore, an object of the present invention is to provide a thermally conductive resin sheet that is excellent in moisture absorption and reflow resistance. In this specification, "moisture absorption reflow resistance" means that even after a moisture absorption reflow test in which a thermally conductive resin sheet is laminated with a metal plate and stored under high temperature and high humidity conditions (e.g., an environment of 85°C and 85% RH for 3 days) and then a reflow test (e.g., 290°C) is performed, the thermally conductive resin sheet has high voltage resistance and does not delaminate at the interface with the metal plate or deform due to foaming. [Means for solving the problem]

[0014] A resin composition according to one embodiment of the present invention is a resin composition comprising a thermoplastic resin and a thermally conductive filler, wherein the thermoplastic resin has a tensile storage modulus at 200° C. (E′(200)) of 8.0×10 7 Pa or more, 1.0×10 10 Pa or less, and the mass increase rate of the resin composition at 85° C. and 85% RH is 0.15% or less. A resin composition according to another embodiment of the present invention is a resin composition comprising a thermoplastic resin and a thermally conductive filler, the thermoplastic resin having a tensile storage modulus at 300° C. (E′(300)) of 4.0×10 7 Pa or more, 1.0×10 9 Pa or less, and the mass increase rate of the resin composition at 85° C. and 85% RH is 0.15% or less. Effect of the Invention

[0015] The thermally conductive resin sheet obtained from the resin composition of the present invention has excellent resistance to moisture absorption and reflow. [Brief description of the drawings]

[0016] [Figure 1] 1 is a cross-sectional SEM image according to an example embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram according to another example of an embodiment of the present invention. [Diagram 3] 13 is a cross-sectional SEM image according to another example of an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments, and various modifications can be made within the scope of the present invention.

[0018] <Configuration of the present invention> The configuration of the present invention will be described below.

[0019] 1.Resin composition The resin composition of the present invention contains a thermoplastic resin and a thermally conductive filler.

[0020] The thermal conductive resin sheet of the present invention preferably has a mass increase rate of 0.15% or less at 85°C and 85% RH. Among them, it is preferably 0% or more and 0.15% or less, more preferably 0% or more and 0.12% or less, and even more preferably 0% or more and 0.10% or less. By having the mass increase rate be equal to or less than the upper limit, it is possible to suppress the moisture absorbed by the resin composition in a humid and hot environment from vaporizing and expanding due to heating in the reflow process, and the generation of foaming inside the thermal conductive resin sheet. Therefore, after performing a moisture absorption reflow test, the voltage resistance is less likely to decrease, the thermal conductivity in the sheet thickness direction is less likely to decrease, and interfacial peeling with the metal plate is less likely to occur. The mass increase rate can be measured by the method described in the Examples. The mass increase rate can be adjusted by the type and content of the thermoplastic resin, the type and content of the thermally conductive filler, etc. However, it is not limited to these.

[0021] Each component constituting the resin composition of the present invention will be described in detail below.

[0022] (1)Thermoplastic resin The tensile storage modulus (E'(200)) of the thermoplastic resin in the present invention at 200°C is 8.0 x 10 7 Pa or more 1.0×10 10 Pa or less is preferable, 8.0×10 7 Pa or more 5.0×10 9 Pa or less is more preferable, and 8.0×10 7 Pa or more 3.0×10 9 Pa or less is more preferable, and 8.0×10 7 Pa or more 2.0×10 9 Pa or less is even more preferable. 8 Pa or more 1.0×10 10 Pa or less is preferable, and 1.0×10 8 Pa or more 5.0×10 9Pa or less is more preferable, and 1.0×10 8 Pa or more 3.0×10 9 Pa or less is more preferable, and 1.0×10 8 Pa or more 2.0×10 9 Pa or less is even more preferable. 8 Pa or more 1.0×10 10 Pa or less is preferable, and 2.0×10 8 Pa or more 5.0×10 9 Pa or less is more preferable, and 2.0×10 8 Pa or more 3.0×10 9 Pa or less is more preferable, and 2.0×10 8 Pa or more 2.0×10 9 Pa or less is even more preferable. 8 Pa or more 1.0×10 10 Pa or less is preferable, and 3.0×10 8 Pa or more 5.0×10 9 Pa or less is more preferable, and 3.0×10 8 Pa or more 3.0×10 9 Pa or less is more preferable, and 3.0×10 8 Pa or more 2.0×10 9 Pa or less is even more preferable. The tensile storage modulus (E'(300)) of the thermoplastic resin of the present invention at 300°C is 4.0 x 10 7 Pa or more 1.0×10 9 Pa or less is preferable, and 4.0×10 7 Pa or more 6.0×10 8 Pa or less is more preferable, and 4.0×10 7 Pa or more 4.0×10 8 Pa or less is more preferable, and 4.0×10 7 Pa or more 2.0×10 8 Pa or less is even more preferable. 7 Pa or more 1.0×10 9 Pa or less is preferable, and 6.0×10 7 Pa or more 6.0×10 8 Pa or less is more preferable, and 6.0×10 7 Pa or more 4.0×10 8 Pa or less is more preferable, and 6.0×107 Pa or more 2.0×10 8 Pa or less is even more preferable. 7 Pa or more 1.0×10 9 Pa or less is preferable, 8.0×10 7 Pa or more 6.0×10 8 Pa or less is more preferable, and 8.0×10 7 Pa or more 4.0×10 8 Pa or less is more preferable, and 8.0×10 7 Pa or more 2.0×10 8 Pa or less is even more preferable. 8 Pa or more 1.0×10 9 Pa or less is preferable, and 1.0×10 8 Pa or more 6.0×10 8 Pa or less is more preferable, and 1.0×10 8 Pa or more 4.0×10 8 Pa or less is more preferable, and 1.0×10 8 Pa or more 2.0×10 8 Pa or less is even more preferable. By having the tensile storage modulus (E'(200)) within the above range, even if the resin composition absorbs moisture in a humid and hot environment and the moisture evaporates due to heating in the reflow process, it is possible to suppress the generation of bubbles inside the thermally conductive resin sheet or at the interface between the sheet and the metal plate, and to suppress the generated bubbles from expanding significantly. Therefore, it is possible to suppress the decrease in thermal conductivity and the decrease in voltage resistance due to the generation of bubbles, and also to suppress the peeling of the thermally conductive resin sheet from the metal plate. In addition, by having the tensile storage modulus (E'(300)) within the above range, the reflow resistance is improved, and the decrease in thermal conductivity and the decrease in voltage resistance due to the generation of bubbles can be further suppressed, and peeling of the thermally conductive resin sheet from the metal plate can also be further suppressed. The tensile storage modulus (E'(200) and E'(300)) can be measured by the method described in the Examples.

[0023] It is preferable that the thermoplastic resin used in the thermally conductive resin sheet of the present invention does not cause abnormalities even under the reflow conditions of the heat dissipating circuit board at 290° C. for 5 minutes. To satisfy this condition, it is preferable to use a non-crystalline thermoplastic resin having a glass transition temperature (Tg) of at least 300° C. or more, or a crystalline thermoplastic resin having a melting point (Tm) of at least 300° C. or more.

[0024] In the present invention, the term "non-crystalline thermoplastic resin" refers to a thermoplastic resin that does not have a melting point, whereas the term "crystalline thermoplastic resin" refers to a thermoplastic resin that has a melting point.

[0025] Examples of heat-resistant amorphous thermoplastic resins available as commercially available raw materials include polycarbonate resin (Tg: 152°C), modified polyphenylene ether resin (Tg: 211°C), polysulfone resin (Tg: 190°C), polyphenylsulfone resin (Tg: 220°C), polyethersulfone resin (Tg: 225°C), polyetherimide resin (Tg: 217°C), and the like. However, none of these commercially available heat-resistant amorphous thermoplastic resins has a glass transition temperature far below 300°C or higher. Thermoplastic polyimide resins with a glass transition temperature of 300° C. or higher are commercially available. However, the moldable temperature of the thermoplastic polyimide resin is very high, and the melt viscosity at the moldable temperature is very high, making it difficult to fill a large amount of thermally conductive filler. Furthermore, since the molecular structure contains an imide group, it is highly hygroscopic, and therefore is not suitable for use as the main component of the thermoplastic resin of the present invention.

[0026] For these reasons, the main component of the thermoplastic resin used as the matrix resin in the present invention is preferably a crystalline thermoplastic resin having a melting point of 300° C. or higher. In the present invention, the "major component of thermoplastic resin" means a component that accounts for 50% by mass or more of the thermoplastic resin used as the matrix resin in the present invention, particularly 60% by mass or more, particularly 70% by mass or more, particularly 80% by mass or more, particularly 90% by mass or more (including 100% by mass).

[0027] The melting point of the crystalline thermoplastic resin can be measured by the method specified in ISO 1183. Specifically, it can be determined from the crystal melting peak temperature during the second heating period when the crystalline thermoplastic resin is measured by a differential scanning calorimeter (DSC). As the crystalline thermoplastic resin in the present invention, it is preferable to use one in which at least an endothermic peak due to crystal melting can be clearly confirmed and the peak top temperature is 300° C. or higher. In addition, when a resin composition containing added thermally conductive fillers is measured by a differential scanning calorimeter (DSC), there is no significant difference in the melting point, except in cases where the addition of the thermally conductive filler accelerates the deterioration of the matrix resin during heat molding.

[0028] The melting point of the crystalline thermoplastic resin in the present invention is more preferably 310°C or higher, more preferably 320°C or higher, and even more preferably 330°C or higher, from the viewpoint of moisture absorption reflow resistance at 290°C. On the other hand, the upper limit of the melting point is not particularly limited. Among them, from the viewpoint of moldability and productivity, it is more preferably 380°C or lower, more preferably 370°C or lower, and even more preferably 360°C or lower. If the melting point is 300°C or higher, the elastic modulus of the resin raw material decreases during moisture absorption reflow at 290°C, causing the resin to flow and deform, or the elastic distortion of the resin layer is restored, thereby reducing the risk of the surface appearance of the thermally conductive resin sheet deteriorating, the thickness of the thermally conductive resin sheet becoming uneven, and sufficient adhesive strength with the metal substrate not being obtained. In addition, the possibility of foaming in the thermally conductive resin sheet due to the expansion of moisture absorbed by the resin composition in a humid and hot environment can be reduced. In addition, when foaming occurs inside the thermally conductive resin sheet, there is a risk of a significant decrease in the breakdown voltage, but this can be reduced. In addition, when a heat dissipating metal material is laminated on one surface of the thermally conductive resin sheet, if foaming occurs near the interface between the heat dissipating metal material and the thermally conductive resin sheet, the heat dissipating metal material may peel off and the thermal conductivity may be significantly reduced, but this can be reduced. Furthermore, when a conductive circuit pattern is formed on the other surface of the thermally conductive resin sheet, if foaming occurs near the interface between the conductive circuit pattern and the thermally conductive resin sheet, the conductive circuit pattern may peel off or fall off, causing an abnormality in the electric circuit or a significant decrease in the thermal conductivity of the thermally conductive resin sheet, but this can be reduced.

[0029] Specific examples of heat-resistant crystalline thermoplastic resins include polybutylene terephthalate resin (PBT, melting point: 224°C), polyamide 6 (nylon 6, melting point: 225°C), polyamide 66 (nylon 66, melting point: 265°C), liquid crystal polymer (LCP, melting point: 320°C to 344°C), polyether ketone resin (melting point: 303°C to 400°C), polytetrafluoroethylene resin (PTFE, melting point: 327°C), tetrafluoroethylene-perfluoroalkoxyethylene copolymer resin (PFA, melting point: 302°C to 310°C), tetrafluoroethylene-hexafluoropropylene copolymer resin (FEP, melting point: 250°C to 290°C), and the like. Among them, the crystalline thermoplastic resin used in the present invention includes liquid crystal polymers, polyether ketone resins, PTFE, and PFA, because they have a melting point of 300° C. or higher.

[0030] Among crystalline thermoplastic resins having a melting point of 300° C. or higher, liquid crystal polymers and / or polyether ketone resins are preferred from the standpoint of moldability and the like. Among the above, polyether ketone resins are preferred from the viewpoint of adhesion to heat-dissipating metal materials such as copper plates.

[0031] The polyether ketone resin that can be used in the present invention is a general term for thermoplastic resins having a repeating unit represented by formula (1) (wherein m and n are 1 or 2).

[0032] [ka]

[0033] Examples of polyetherketone resins include polyetherketone (PEK; m=1, n=1, melting point 373°C), polyetheretherketone (PEEK; m=2, n=1, melting point 343°C), polyetherketoneketone (PEKK; m=1, n=2, melting point 303°C to 400°C), polyetheretherketoneketone (PEEKK; m=2, n=2, melting point 358°C), and polyetherketoneetherketoneketone (PEKEKK; copolymer containing both m=1, n=1 structural units and m=1, n=2 structural units, melting point 387°C). All of these are available as commercially available raw materials.

[0034] Among polyether ketone resins, polyether ether ketone (PEEK) can be particularly preferably used, taking into consideration a variety of factors, including that it has a sufficiently high melting point and a relatively low molding processing temperature, allowing the molding cycle to be shortened, that it has a continuous heat resistance temperature of 200°C or higher, demonstrating that it can be used in heat-resistant applications without any problems, that various grades are available in terms of melt viscosity related to molding processability, that it has the most chemically stable structure among polyether ketone resins and is also excellent in hot water resistance and chemical resistance, and that its price has become reasonable due to its use in a wide range of applications.

[0035] Various commercial PEEK products can be used. For example, products with various melt viscosities are available from various companies, such as "KetaSpire (registered trademark)" manufactured by Solvay, "Vestakeep (registered trademark)" manufactured by Daicel-Evonik, and "Victrex PEEK" manufactured by Victrex. These PEEK raw materials may be used in the form of a single grade, or in the form of a blend of multiple grades having different melt viscosities, etc.

[0036] The melt viscosity of the crystalline thermoplastic resin in the present invention is not particularly limited. In particular, since a relatively large amount of thermally conductive filler is blended, in order to facilitate hot molding, it is preferably 0.60 kPa·s or less, and more preferably 0.30 kPa·s or less. By having the melt viscosity within the above range, it is not necessary to set the temperature of the molding machine excessively high, and deterioration of the raw material can be suppressed. On the other hand, the lower limit of the melt viscosity is not particularly limited. In particular, 0.01 kPa·s or more is preferable. The melt viscosity is based on ASTM D3835 and is measured at a shear rate of 1000 s -1 These values ​​were measured at a temperature of 400°C.

[0037] From the viewpoint of long-term durability in a heated environment, the mass average molecular weight (Mw) of the crystalline thermoplastic resin is preferably 48,000 or more, more preferably 49,000 or more, and even more preferably 50,000 or more. On the other hand, from the viewpoint of moldability, it is preferably 120,000 or less, more preferably 110,000 or less, and even more preferably 100,000 or less. The MFR of the crystalline thermoplastic resin is preferably 8 g / 10 min or more, more preferably 9 g / 10 min or more, and even more preferably 10 g / 10 min or more, from the viewpoint of moldability and the difficulty of forming voids between the resin and the added thermally conductive filler. On the other hand, from the viewpoint of long-term durability in a heated environment, the MFR is preferably 180 g / 10 min or less, more preferably 170 g / 10 min or less, and even more preferably 160 g / 10 min or less. The MFR is a value measured at 380°C and 5kgf in accordance with JIS K7210 (2014).

[0038] When polyether ether ketone (PEEK) is used as the crystalline thermoplastic resin of the present invention, it may be blended with other thermoplastic resins. The type of other thermoplastic resin is not particularly limited. Among them, the other thermoplastic resin is preferably a compatible resin that has the effect of compensating for the performance that is insufficient when only polyether ether ketone is used for the purpose of the present invention. When other thermoplastic resins are blended, it is preferable that the melting point of the blended resin is 300° C. or higher.

[0039] As the compatible resin, polyetherimide (PEI) is more preferable. By combining PEEK and PEI, not only can the crystallinity (heat of crystal fusion) of PEEK be adjusted, but also the glass transition temperature when the resin composition is in an amorphous state can be increased in conjunction with the adjustment of the crystallization speed of PEEK (Tg of PEEK is 143°C, while Tg of PEI is 217°C). Since PEI is an amorphous resin, the melting point of the resin itself does not change even when PEEK and PEI are combined. In addition, in the present invention, by using PEI which has an imide group and is amorphous, it is possible to improve the adhesion to heat dissipating metal materials such as copper plates.

[0040] The amount of PEI added is preferably 50% by mass or less, with the total amount of the resin composition being 100% by mass. By adding 50% by mass or less of PEI, the heat resistance in a moisture absorption reflow test can be maintained by the crystallinity of PEEK, while the adhesion to heat dissipating metal materials can be improved.

[0041] (2) Thermally conductive filler The resin composition of the present invention preferably contains an electrically insulating, thermally conductive filler in order to improve the thermal conductivity of the resulting thermally conductive resin sheet, suppress the linear expansion coefficient, and ensure the insulating performance. By suppressing the linear expansion coefficient of the thermally conductive resin sheet of the present invention, for example, in a configuration in which the thermally conductive resin sheet of the present invention is laminated and integrated with a different material such as a copper plate, interfacial peeling between the thermally conductive resin sheet and the different material can be suppressed even when the temperature is repeatedly changed between low temperatures (e.g., -40°C) and high temperatures (e.g., 200°C). In the present invention, the thermally conductive filler refers to particles having a thermal conductivity of 1.0 W / m·K or more, and preferably 1.2 W / m·K or more.

[0042] Examples of the thermally conductive filler include an electrically insulating filler consisting only of carbon, a metal carbide or semi-metal carbide, a metal oxide or semi-metal oxide, and a metal nitride or semi-metal nitride.

[0043] An example of an electrically insulating filler that is made only of carbon is diamond (thermal conductivity: approximately 2000 W / m·K). Examples of metal carbides or semi-metal carbides include silicon carbide (thermal conductivity: about 60 to 270 W / m·K), titanium carbide (thermal conductivity: about 21 W / m·K), and tungsten carbide (thermal conductivity: about 120 W / m·K).

[0044] Examples of metal oxides or semi-metal oxides include magnesium oxide (thermal conductivity: about 40 W / m·K), aluminum oxide (thermal conductivity: about 20 to 35 W / m·K), silicon oxide (thermal conductivity: about 1.2 W / m·K), zinc oxide (thermal conductivity: about 54 W / m·K), yttrium oxide (thermal conductivity: about 27 W / m·K), zirconium oxide (thermal conductivity: about 3 W / m·K), ytterbium oxide (thermal conductivity: about 38.5 W / m·K), beryllium oxide (thermal conductivity: about 250 W / m·K), and "sialon" (ceramics composed of silicon, aluminum, oxygen, and nitrogen, thermal conductivity: about 21 W / m·K). Examples of metal nitrides or semi-metal nitrides include boron nitride (thermal conductivity in the plane direction of plate-like particles of hexagonal boron nitride (h-BN): approximately 200 to 500 W / m K), aluminum nitride (thermal conductivity: approximately 160 to 285 W / m K), and silicon nitride (thermal conductivity: approximately 30 to 80 W / m K).

[0045] These thermally conductive fillers may be used alone or in combination of two or more.

[0046] In addition, when the thermally conductive resin sheet of the present invention is used for a power semiconductor device, electrical insulation is required, and therefore, it is preferable that the thermally conductive filler is an inorganic compound having excellent insulation properties. 13 A resistance of 10 Ω·cm or more is preferable, and 10 14 Ω·cm or more is more preferable. Among them, metal oxides, semi-metal oxides, metal nitrides, and semi-metal nitrides are preferred because they can easily provide the thermally conductive resin sheet with sufficient electrical insulation. Specific examples of such thermally conductive fillers include aluminum oxide (Al2O3, volume resistivity: >10 14 Ω·cm), Aluminum Nitride (AlN, volume resistivity:>10 14 Ω·cm), Boron Nitride (BN, volume resistivity:>10 14 Ω·cm), Silicon Nitride (Si3N4, volume resistivity:>10 14 Ω·cm), Silica (SiO2, Volume resistivity:>10 14 Ω·cm). Among these, aluminum oxide, aluminum nitride, boron nitride, and silica are preferred, with aluminum oxide and boron nitride being particularly preferred since they can impart high insulating properties to the thermally conductive resin sheet.

[0047] Among the above, it is preferable that the thermally conductive filler of the present invention contains boron nitride, since it has little problem with moisture absorption during hot molding, is low in toxicity, can efficiently increase thermal conductivity, and can impart high insulating properties to the thermally conductive resin sheet. The boron nitride preferably contains, as a main component, boron nitride agglomerated particles formed by agglomeration of primary particles of boron nitride. "Containing, as a main component, boron nitride agglomerated particles" means that the boron nitride agglomerated particles account for 50 mass% or more of the boron nitride, particularly 70 mass% or more, particularly 80 mass% or more, particularly 90 mass% or more (including 100 mass%).

[0048] In addition, boron nitride may be used in combination with other thermally conductive fillers. However, the heat transfer behavior in the thermally conductive resin sheet does not depend solely on the thermal conductivity inside the thermally conductive filler, as described later. Therefore, even if diamond particles or the like, which have extremely high thermal conductivity but are also extremely expensive, are used among the particles exemplified above, the thermal conductivity in the thickness direction of the thermally conductive resin sheet does not increase extremely. Therefore, when boron nitride is used in combination with other thermally conductive fillers, the main focus is on reducing the cost of the composition. Therefore, it is preferable to appropriately select from magnesium oxide, aluminum oxide, tungsten carbide, silicon carbide, aluminum nitride, etc., as the thermally conductive filler to be used in combination with boron nitride, from the viewpoints of relatively low cost and relatively high thermal conductivity.

[0049] The thermally conductive filler may be in the form of irregular particles, spheres, whiskers, fibers, plates, or an aggregate or mixture thereof. In particular, the shape of the thermally conductive filler of the present invention is preferably spherical. The term "spherical" generally means that the aspect ratio (ratio of major axis to minor axis) is 1 or more and 2 or less, preferably 1 or more and 1.75 or less, more preferably 1 or more and 1.5 or less, and even more preferably 1 or more and 1.4 or less. The aspect ratio can be determined by randomly selecting 200 or more particles from an image of the cross section of a thermally conductive resin sheet taken with a SEM, determining the ratio of the long axis to the short axis of each particle, and calculating the average value.

[0050] The thermally conductive filler of the present invention preferably contains boron nitride agglomerated particles (also called "secondary particles") formed by agglomeration of tabular boron nitride particles (also called "primary particles"). Examples of the primary particles include cubic boron nitride, hexagonal boron nitride (h-BN), etc. Among these, hexagonal boron nitride is preferred from the viewpoint of improving thermal conductivity.

[0051] Hexagonal boron nitride particles have a shape called a plate or scale shape, and are characterized by extremely high thermal conductivity in the plate surface direction (approximately 200 to 500 W / m·K). However, due to this shape, when a resin sheet is produced by a normal thermoplastic resin molding method (for example, sheet extrusion using an extruder equipped with a twin screw and a T-die), most of the added boron nitride is oriented parallel to the surface of the resin sheet. Therefore, the thermal conductivity in the thickness direction of the resin sheet may be lower than when a spherical filler with a similar thermal conductivity is added. Therefore, by agglomerating the plate-shaped boron nitride particles (primary particles) to form boron nitride agglomerated particles (secondary particles), the orientation of the plate-shaped particles in a specific direction can be suppressed, and the thermal conductivity in the thickness direction can also be improved.

[0052] Examples of the aggregate structure of the boron nitride aggregated particles include a cabbage structure and a card house structure. Among these, the card house structure is preferred from the viewpoint of improving thermal conductivity. The aggregate structure of the boron nitride aggregated particles can be confirmed by a scanning electron microscope (SEM).

[0053] The cabbage structure refers to a spherical aggregation of flat primary particles like a cabbage structure. When the cabbage structure aggregated particles are added to a resin sheet, the boron nitride primary particles constituting the boron nitride aggregated particles are not oriented only in the surface direction of the thermal conductive resin sheet, so that the thermal conductivity in the thickness direction of the sheet can be easily increased compared to the case where the boron nitride primary particles are simply added. However, when viewed in the radial direction from the approximate center of the cabbage structure aggregated particles, most of the primary particles have their flat surfaces oriented perpendicular to the radial direction. Therefore, although some primary particles are indeed oriented in the thickness direction of the sheet or oriented closer to the thickness direction, only a limited portion of the particles can effectively conduct heat in the thickness direction. A cross-sectional SEM image of a thermoplastic resin containing cabbage-structured agglomerated particles of boron nitride, which was then heated and pressed, is shown in Figure 1. Referring to Figure 1, it can be seen that many of the primary particles of boron nitride are oriented at a shallow angle to the surface direction of the resin sheet.

[0054] On the other hand, the house of cards structure is a structure in which plate-shaped particles are not oriented and are stacked in a complex manner, as described in "Ceramics 43 No. 2" (published by the Ceramic Society of Japan in 2008). More specifically, it is a structure in which the flat surface of the primary particles that form the aggregate particle is in contact with the end surface of other primary particles that exist within the aggregate particle. A schematic diagram of the house of cards structure is shown in Figure 2. The card-house structured aggregated particles have a very high breaking strength due to their structure, and do not break even during the pressurizing process performed during the molding of the heat-dissipating resin sheet. Therefore, the primary particles that are usually oriented in the longitudinal direction of the heat-dissipating resin sheet can be made to exist in random directions. Therefore, high thermal conductivity can be achieved not only in the longitudinal direction of the heat-dissipating resin sheet, but also in the thickness direction. Figure 3 shows a cross-sectional SEM image of house-of-cards structured boron nitride agglomerated particles added to a thermoplastic resin and then hot-press molded. Compared to Figure 1, where the same mass of cabbage-structured boron nitride agglomerated particles was added, it can be seen that there are more particles oriented at a shallow angle to the thickness direction of the thermal conductive resin sheet. In this way, the house-of-cards structured boron nitride agglomerated particles have more primary particles oriented in the thickness direction than the cabbage-structured boron nitride agglomerated particles, and therefore can conduct heat more effectively in the thickness direction, further increasing the thermal conductivity in the thickness direction. Incidentally, boron nitride agglomerated particles having a house-of-cards structure can be produced, for example, by the method described in International Publication No. 2015 / 119198.

[0055] When using boron nitride agglomerated particles having a house of cards structure, the particles may be surface-treated with a surface treatment agent. As an example of the surface treatment agent, a known surface treatment such as a silane coupling treatment can be used. In general, there is often no direct affinity or adhesion between a thermally conductive filler and a thermoplastic resin, and this is also the case when boron nitride agglomerated particles having a house of cards structure are used as a thermally conductive filler. It is believed that by increasing the adhesion at the interface between the thermally conductive filler and the matrix resin by chemical treatment, the attenuation of thermal conductivity at the interface can be further reduced.

[0056] By using boron nitride agglomerated particles as the thermally conductive filler of the present invention, the particle size can be made larger than that of a thermally conductive filler that uses primary particles as is. By increasing the particle size of the thermally conductive filler, the heat transfer path between the thermally conductive fillers via the thermoplastic resin with low thermal conductivity can be reduced, and therefore the increase in thermal resistance in the heat transfer path in the thickness direction can be reduced.

[0057] From the above viewpoints, the lower limit of the maximum particle diameter Dmax based on volume of the thermally conductive filler (hereinafter also referred to as "maximum particle diameter") is preferably 20 μm or more, more preferably 30 μm or more, and even more preferably 50 μm or more. On the other hand, the upper limit of the maximum particle diameter Dmax is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, and even more preferably 90 μm or less.

[0058] The lower limit of the volume-based average particle diameter D50 of the thermally conductive filler is preferably 2 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and even more preferably 20 μm or more. On the other hand, the upper limit of the average particle diameter D50 is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, and even more preferably 80 μm or less.

[0059] By making the maximum particle size of the thermally conductive filler equal to or less than the upper limit, when the thermally conductive filler is contained in the matrix resin, the interface between the matrix resin and the thermally conductive filler is reduced, resulting in a smaller thermal resistance, and high thermal conductivity can be achieved, while a good quality film can be formed without surface roughness, etc. By making the maximum particle size equal to or more than the lower limit, a sufficient thermal conductivity improving effect as a thermally conductive filler required for power semiconductor devices can be obtained.

[0060] In addition, it is considered that the influence of the thermal resistance at the interface between the matrix resin and the thermally conductive filler on the thickness of the thermally conductive resin sheet becomes significant when the size of the thermally conductive filler is 1 / 10 or less of the thickness of the thermally conductive resin sheet. In particular, in the case of power semiconductor devices, thermally conductive resin sheets with a thickness of 100 μm to 300 μm are often applied, so from the viewpoint of thermal conductivity, it is preferable that the maximum particle size Dmax based on volume of the thermally conductive filler is larger than the above lower limit. Furthermore, by having the maximum particle diameter Dmax of the thermally conductive filler be equal to or greater than the above lower limit, not only is the thermal conductivity attenuation caused by the interface between the thermally conductive filler and the matrix resin suppressed, but the number of required thermally conductive paths between particles is reduced, increasing the probability of connection from one side to the other side in the thickness direction of the thermally conductive resin sheet. Furthermore, by having the maximum particle size Dmax of the thermally conductive filler be equal to or greater than the above lower limit, the interfacial area between the matrix resin and the thermally conductive filler is smaller than when the same mass of particles having a Dmax smaller than the above lower limit is used. This makes it possible to reduce the occurrence of voids that tend to occur at the interface between the matrix resin and the thermally conductive filler in the thermally conductive resin sheet, making it easier to obtain excellent voltage resistance characteristics. On the other hand, by having the volume-based maximum particle diameter Dmax of the thermally conductive filler be equal to or less than the above upper limit, protrusion of the thermally conductive filler onto the surface of the thermally conductive resin sheet is suppressed, and a good surface shape without surface roughness is obtained. Therefore, when producing a sheet bonded to a copper substrate, sufficient adhesion can be obtained, and excellent voltage resistance characteristics can be obtained.

[0061] The ratio (Dmax / thickness) of the size (Dmax) of the thermally conductive filler to the thickness of the thermally conductive resin sheet is preferably 0.3 or more and 1.0 or less, more preferably 0.35 or more and 0.95 or less, and even more preferably 0.4 or more and 0.9 or less.

[0062] The maximum particle size Dmax and the average particle size D50 of the thermally conductive filler can be measured, for example, by the following method. For a sample in which a thermally conductive filler is dispersed in a solvent, specifically, a sample in which a thermally conductive filler is dispersed in a pure water medium containing sodium hexametaphosphate as a dispersion stabilizer, the particle size distribution is measured using a laser diffraction / scattering particle size distribution analyzer LA-920 (manufactured by Horiba, Ltd.), and the maximum particle size Dmax and average particle size D50 of the thermally conductive filler can be obtained from the obtained particle size distribution. The maximum particle size and the average particle size can also be determined using a dry particle size distribution measuring device such as Morphologi G3 (manufactured by Malvern Instruments). The maximum particle size Dmax and average particle size D50 of the thermally conductive filler added to the thermoplastic resin can also be measured in the same manner as above by dissolving and removing the thermoplastic resin in a solvent (including a heated solvent), or by physically removing the filler after swelling it to reduce the adhesive strength with the thermally conductive filler, and further by heating the resin component in air to incinerate it and remove it.

[0063] (3) Content of each ingredient The content of the thermoplastic resin in 100% by mass of the resin composition of the present invention is preferably 15% by mass or more and 40% by mass or less, more preferably 15% by mass or more and 35% by mass or less, and more preferably 20% by mass or more and 40% by mass or less, more preferably 20% by mass or more and 35% by mass or less. The content of the thermally conductive filler in 100% by mass of the resin composition of the present invention is preferably 60% by mass to 85% by mass, more preferably 60% by mass to 80% by mass, and more preferably 65% ​​by mass to 85% by mass, more preferably 65% ​​by mass to 80% by mass. By making the content of the thermally conductive filler equal to or greater than the lower limit, the thermal conductivity improving effect and the linear expansion coefficient controlling effect due to the thermally conductive filler are satisfactorily exhibited, whereas by making the content of the thermally conductive filler equal to or less than the upper limit, the moldability of the resin composition and the interfacial adhesion with different materials are improved.

[0064] In general, the compounding ratio of a thermally conductive resin composition is often specified by the volume fraction of the matrix resin and the thermally conductive filler (hence, the area ratio in the cross section of the thermally conductive resin sheet). The thermal conductivity in the thickness direction of the thermally conductive resin sheet is not determined only by the volume fraction, but is affected by various factors such as the above-mentioned preferred particle size, particle orientation state, and particle shape, so in the present invention, the mass fraction is used for convenience in practical compounding. In particular, when using boron nitride agglomerated particles with a house-of-cards structure as a thermally conductive filler, the particles are not only characterized by the house-of-cards structure as an internal structure, but also form a large number of tabular boron nitride primary particles oriented in the radial direction on the particle surface in a protruding state, which is called a burr shape or a confetti shape, and the protrusions of adjacent house-of-cards structure particles come into physical contact with each other, forming a heat transfer path with low thermal resistance in the thickness direction. Therefore, it may not be easy to determine the respective volume fractions of the matrix resin and the thermally conductive filler by observation with a normal scanning electron microscope (SEM). Furthermore, when the amount of boron nitride agglomerated particles with a house-of-cards structure added is increased, the pressure applied during the hot press molding of the resin composition causes the particles to deform at the contact points, rather than contacting each other as spherical particles, and the contact points are observed to be in linear, i.e., planar, contact. In such a contact state, the addition of boron nitride with a house-of-cards structure enables the formation of an efficient heat transfer path. However, even in such a case, it is not easy to determine the respective volume fractions of the matrix resin and the thermally conductive filler by SEM observation.

[0065] The thermally conductive filler of the present invention preferably contains 50 mass% or more of boron nitride agglomerated particles, more preferably 60 mass% or more, even more preferably 70 mass% or more, and even more preferably 80 mass% or more, based on 100 mass% of the thermally conductive filler. The entire amount (100 mass%) of the thermally conductive filler may be boron nitride agglomerated particles. When the content of the boron nitride agglomerated particles is equal to or more than the above lower limit, the thermal conductivity in the thickness direction of the thermal conductive resin sheet is increased.

[0066] The resin composition of the present invention may contain other components in addition to the crystalline thermoplastic resin and the thermally conductive filler, although it is preferable that the resin composition does not contain other components from the viewpoint of increasing thermal conductivity. Other components include various antioxidants such as phosphorus-based and phenol-based, phenol acrylate-based and other process stabilizers, heat stabilizers, hindered amine radical scavengers (HAAS), impact modifiers, processing aids, metal deactivators, copper inhibitors, antistatic agents, flame retardants, additives such as silane coupling agents that improve the affinity at the interface between the thermally conductive filler and the thermoplastic resin, as well as additives such as silane coupling agents that can be expected to increase the adhesive strength between the resin sheet and the metal plate material, extenders, etc. When these additives are used, the amount of addition may be within the range of the amount usually used for these purposes.

[0067] 2.Thermal conductive resin sheet The thermally conductive resin sheet of the present invention is made of the above-mentioned resin composition, has excellent moisture absorption reflow resistance, and is less susceptible to interfacial peeling due to thermal expansion and contraction when laminated with a metal plate.

[0068] The thermal conductivity of the thermal conductive resin sheet in the thickness direction at 25° C. is preferably at least 5.0 W / m K, more preferably at least 7.0 W / m K, and even more preferably at least 9.0 W / m K. When the thermal conductivity in the thickness direction is equal to or greater than the above lower limit, the sheet can be suitably used in power semiconductor devices that operate at high temperatures. The thermal conductivity can be adjusted by the type of thermoplastic resin and its physical properties such as melt viscosity, the type and content of the thermally conductive filler, the method of mixing the thermoplastic resin and the thermally conductive filler, and the conditions in the heating and kneading process described below.

[0069] Moreover, the thermal conductive resin sheet of the present invention preferably has a thermal conductivity in the thickness direction at 200° C. of 90% or more, and more preferably 92% or more, of the thermal conductivity in the thickness direction at 25° C. Since the thermal conductivity in the thickness direction at 200° C. is equal to or more than the above lower limit, the sheet can be suitably used in power semiconductor devices and the like that are operated at high temperatures.

[0070] The lower limit of the thickness of the thermally conductive resin sheet is preferably 50 μm or more, more preferably 60 μm or more, and even more preferably 70 μm or more. On the other hand, the upper limit of the thickness is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 160 μm or less. By making the thickness of the thermally conductive resin sheet 50 μm or more, sufficient voltage resistance characteristics can be ensured. On the other hand, by making the thickness 300 μm or less, it is possible to achieve miniaturization and thinning, particularly when the thermally conductive resin sheet is used in a power semiconductor device, and also, compared to an insulating thermally conductive layer made of a ceramic material, it is possible to obtain the effect of reducing the thermal resistance in the thickness direction by making the thickness thinner.

[0071] In the thermally conductive resin sheet of the present invention, in order to reduce the anisotropy of thermal conductivity and increase the thermal conductivity in the thickness direction, it is preferable to reduce the orientation of the primary particles of the thermally conductive filler. The orientation of the primary particles can be evaluated by measuring the thermally conductive resin sheet by X-ray diffraction and calculating the ratio I(002) / I(100), where I(002) is the diffraction peak intensity of the (002) plane and I(100) is the diffraction peak intensity of the (100) plane. The ratio "I(002) / I(100)" is preferably 20.0 or less, more preferably 17.0 or less, and even more preferably 15.0 or less. If the ratio exceeds 20.0, the thermally conductive filler collapses in the melt-kneading process, or is excessively crushed in the pressurizing process, resulting in a large amount of thermally conductive filler that is parallel to the surface direction of the thermally conductive resin sheet or forms a small angle with the surface direction. In this case, even if the content of the thermally conductive filler is increased, it is difficult to increase the thermal conductivity in the thickness direction. The lower limit of the ratio "I(002) / I(100)" is not particularly limited. For example, when using boron nitride agglomerated particles having a card-house structure as the thermally conductive filler, the ratio "I(002) / I(100)" of the particles alone is about 4.5 to 6.6, so 4.5 is considered to be the lower limit, except when intentional orientation is performed.

[0072] From the viewpoint of simplifying the manufacturing process, it is preferable to adjust the orientation of the primary particles of the thermally conductive filler without intentionally performing an orientation operation. The orientation can be adjusted, for example, by appropriately changing the type and physical properties such as melt viscosity of the thermoplastic resin, the type and content of the thermally conductive filler, the method of mixing the thermoplastic resin and the thermally conductive filler, the conditions in the heating and kneading step described later, etc.

[0073] 3. Manufacturing method of thermally conductive resin sheet Hereinafter, as an example of the method for producing the thermally conductive resin sheet of the present invention, there can be mentioned a method including a heating and kneading step of heating and kneading a thermoplastic resin and a thermally conductive filler to obtain a resin composition, and a press molding step of pressing the resin composition with a heating body to form a sheet. However, the method for producing the thermally conductive resin sheet of the present invention is not limited to the following manufacturing method.

[0074] (1) Heat mixing process In the heat-kneading step, the thermoplastic resin and the thermally conductive filler are melt-kneaded by heating. In the heat-kneading step, the thermoplastic resin and the thermally conductive filler can be put into a processing machine and melt-kneaded. The processing machine used in the heat kneading step may be one generally used for the purpose of kneading a thermally conductive filler or various additives into a resin, such as a continuous kneader, a plastomill kneader, a co-rotating twin screw extruder kneader, a counter-rotating twin screw extruder kneader, or a single screw extruder kneader. The melt-kneading temperature is preferably set to 370°C to 430°C, more preferably 380°C to 420°C, as the temperature of the molding machine (in the case of an extruder-type melt-kneading device, the temperature of the cylinder heater, etc.). By setting the melt-kneading temperature at 370°C or higher, the resin viscosity is sufficiently reduced, and the load on the molding machine can be suppressed from increasing. Furthermore, the thermal conductive filler can be prevented from shear fracture during kneading, so that the thermal conductivity of the obtained thermal conductive resin sheet is good. On the other hand, by setting the melt-kneading temperature at 450°C or lower, the deterioration of the resin itself and the deterioration of the physical properties of the molded thermal conductive resin sheet can be suppressed.

[0075] (2) Press molding process The resin composition of the present invention that has been heated and melted and kneaded often has a lump-like or powder-like shape even after the heating and kneading process, because the resin composition contains a large amount of thermally conductive filler. Therefore, it is often difficult to manufacture the resin composition in a process that is continuous with the melt-kneading process and then wound up, as in the case of sheet molding of ordinary thermoplastic resin compositions. Therefore, in the present invention, it is preferable to make a sheet from the lump-like or powder-like mixture obtained above by press molding, which is a batch process. However, the manufacturing method of the thermally conductive resin sheet of the present invention is not limited to batch pressing, and it is considered that it is possible to manufacture the resin sheet as a continuous sheet if there is a sheet forming device using a steel belt method that can perform continuous molding at a certain level of high temperature and pressure.

[0076] In the press molding, which is a batch process, various known press machines for molding thermoplastic resins can be used. From the viewpoint of preventing deterioration of the resin during the heat press, it is particularly preferable to use a vacuum press machine capable of reducing the amount of oxygen in the press machine during heating, or a press machine equipped with a nitrogen replacement device. In the pressing step, in addition to the purpose of making the melt-kneaded product into a sheet body with a uniform thickness, it is preferable to set the pressurizing pressure for the purpose of bonding the added thermally conductive fillers together to form a heat path, and for the purpose of eliminating voids and gaps in the sheet. From this viewpoint, the pressure in the pressing step is usually 8 MPa or more, preferably 9 MPa or more, and more preferably 10 MPa or more, as the actual pressure applied to the sample. Also, it is preferably 50 MPa or less, more preferably 40 MPa or less, and even more preferably 30 MPa or less. By setting the pressure during pressing to the above upper limit value or less, it is possible to prevent the thermally conductive filler from being crushed, and a thermally conductive resin sheet with high thermal conductivity can be obtained. In addition, by setting the pressing pressure to the above lower limit value or more, the contact between the thermally conductive fillers is improved, making it easier to form a thermally conductive path, and a sheet with high thermal conductivity can be obtained. In addition, since the gaps in the resin sheet can be reduced, even after the moisture absorption reflow test, a thermally conductive resin sheet with a high dielectric breakdown voltage can be obtained.

[0077] In the press molding step, the temperature of the resin press machine is preferably set to 370°C to 440°C, and more preferably 380°C or higher or 420°C or lower. By performing press molding at this temperature range, the obtained thermally conductive resin sheet can be given good thickness uniformity and high thermal conductivity due to good contact between the added thermally conductive fillers. If the molding temperature is 370°C or higher, the resin viscosity is reduced to a level sufficient for shaping processing, and the molded thermally conductive resin sheet can be given sufficient thickness uniformity. On the other hand, if the set temperature of the press machine is 440°C or lower, deterioration of the resin itself and deterioration of the physical properties of the molded thermally conductive resin sheet can be suppressed.

[0078] The pressurization time is usually 30 seconds or more, preferably 1 minute or more, more preferably 3 minutes or more, and even more preferably 5 minutes or more. Also, it is preferably 1 hour or less, more preferably 30 minutes or less, and even more preferably 15 minutes or less. By being equal to or less than the above upper limit, the manufacturing process time of the thermally conductive resin sheet can be suppressed, and the cycle time can be shortened compared to a thermally conductive resin sheet using a heat-resistant thermosetting resin, and there is a tendency that the production cost can be suppressed. Also, by being equal to or more than the above lower limit, the thickness of the thermally conductive resin sheet can be sufficiently uniform, and internal gaps and voids can be sufficiently removed, and unevenness in thermal conductivity performance and voltage resistance characteristics can be prevented.

[0079] 4.Laminated heat dissipation sheet The laminated heat-dissipating sheet of the present invention is obtained by laminating a heat-dissipating material on one surface of the above-mentioned thermally conductive resin sheet of the present invention. The heat dissipating material is not particularly limited as long as it is made of a material having good thermal conductivity. Among them, in order to increase the thermal conductivity in the laminated structure, it is preferable to use a heat dissipating metal material, and it is more preferable to use a flat metal material. The type of metal material is not particularly limited, but among them, copper plate, aluminum plate, aluminum alloy plate, etc., which have good thermal conductivity and are relatively inexpensive, are preferable.

[0080] When a flat metal material is used as the heat dissipating metal material in the laminated heat dissipation sheet, the thickness of the metal material is preferably 0.03 to 6 mm, and more preferably 0.1 mm or more or 5 mm or less, in order to ensure sufficient heat dissipation.

[0081] Regarding adhesion to heat-dissipating metal materials, the surface of the metal material on the side to be laminated with the thermally conductive resin sheet may be subjected to surface treatments such as soft etching, burnt plating, oxidation-reduction treatment, etc., surface roughening treatments, plating treatments with various metals and metal alloys to ensure adhesion durability, organic surface treatments including silane coupling treatments such as amino-based and mercapto-based, and surface treatments with organic-inorganic composite materials, etc. By carrying out these surface treatments, it is possible to further improve the initial adhesive strength, the durability of the adhesive strength, and the effect of suppressing interfacial peeling after a moisture absorption reflow test.

[0082] On the other hand, the side of the heat dissipating metal material opposite to the side laminated with the thermally conductive resin sheet does not have to be a simple flat plate, and may be subjected to processing such as increasing the surface area in order to ensure a contact area with the cooling medium, which is a gas or liquid. Examples of processing for increasing the surface area include increasing the surface area by roughening the surface with blasting processing, etc., directly forming V-shaped or rectangular grooves or various shapes of unevenness on the heat dissipating metal material by cutting or pressing, joining another metal material that has been further processed to increase the surface area to the heat dissipating metal layer made of a flat metal material by casting processing, diffusion bonding, bolt fastening, soldering, brazing, etc., or embedding metal pins. Furthermore, it is also possible to directly press-laminated a thermally conductive resin sheet onto a heat dissipating metal layer having a cavity for passing a cooling medium. However, since the pressing pressure between the thermally conductive resin sheet and the heat dissipating metal plate is relatively high, in these cases, it is preferable to integrate the laminated and integrated flat metal material and the thermally conductive resin sheet with a grooved metal plate or a metal layer having a cavity for passing a refrigerant in a later process by soldering, brazing, bolt fastening, etc.

[0083] Regarding the lamination and integration of the heat dissipating metal material and the thermally conductive resin sheet in the laminated heat dissipation sheet, press molding, which is a batch process, can be preferably used. In this case, the press equipment and press conditions are the same as the range of press molding conditions for obtaining the above-mentioned thermally conductive resin sheet.

[0084] 5. Heat dissipation circuit board The heat dissipating circuit board of the present invention has the laminated heat dissipating sheet. The heat dissipating circuit board has a configuration in which a heat dissipating metal material is laminated on one surface of the thermally conductive resin sheet of the present invention. Among them, it is preferable that a conductive circuit is laminated on the surface of the thermally conductive resin sheet other than the surface on which the heat dissipating metal material is laminated, by a post-process etching process or the like. The heat dissipating circuit board is preferably configured as an integrated structure of "heat dissipating metal material / thermally conductive resin sheet / conductive circuit." The state before the circuit etching may be, for example, an integrated structure of "heat dissipating metal material / thermally conductive resin sheet / conductive circuit forming metal material," in which the conductive circuit forming metal material is flat and formed on the entire surface of one side of the thermally conductive resin sheet, or formed on a partial area.

[0085] The material of the metal material for forming the conductive circuit is not particularly limited. In particular, it is generally preferable to form the conductive circuit from a copper thin plate having a thickness of 0.05 mm to 1.2 mm in terms of good electrical conductivity, etching properties, cost, etc.

[0086] The dielectric breakdown voltage of the heat dissipating circuit board is preferably 40 kV / mm or more, more preferably 50 kV / mm or more, even more preferably 60 kV / mm or more, and even more preferably 80 kV / mm or more. By having a dielectric breakdown voltage of 40 kV / mm or more, even if the thermal conductive resin sheet has a thickness of, for example, 100 μm, a dielectric breakdown voltage of 4 kV or more can be obtained, and if the dielectric breakdown voltage is 80 kV / mm or more, a dielectric breakdown voltage of 4 kV or more can be obtained even if the thickness is 50 μm. Therefore, while using a thin thermal conductive resin layer that is advantageous in terms of thermal resistance, it has sufficient voltage resistance performance and can suppress the occurrence of dielectric breakdown when a high voltage is applied.

[0087] 6. Power Semiconductor Devices INDUSTRIAL APPLICABILITY The thermally conductive resin sheet of the present invention can be suitably used as a heat dissipation sheet for power semiconductor devices, and can realize a highly reliable power semiconductor module. The power semiconductor device is a power semiconductor device that uses the above-mentioned thermally conductive resin sheet or the above-mentioned laminated heat dissipation sheet, and the above-mentioned thermally conductive resin sheet or the above-mentioned laminated heat dissipation sheet is mounted on a power semiconductor device apparatus as a heat dissipation circuit board. The power semiconductor device has a high thermal conductivity and hence a heat dissipation effect, which allows it to achieve high output and high density with high reliability. In a power semiconductor device, conventionally known materials can be appropriately used for the materials such as aluminum wiring, sealing materials, packaging materials, heat sinks, thermal pastes, and solders other than the thermally conductive resin sheets or laminated heat dissipation sheets.

[0088] <Explanation of terms> In the present invention, when expressed as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y". In addition, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the intention that "greater than X is preferable" or "less than Y is preferable." In the present invention, the term "sheet" conceptually encompasses a sheet, a film, and a tape. EXAMPLES

[0089] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.

[0090] <Examples 1 to 6 and Comparative Examples 1 to 4> The materials used, the production methods, and the measurement conditions and evaluation methods for the thermally conductive resin sheets in Examples 1 to 6 and Comparative Examples 1 to 4 are as follows.

[0091] [Materials used] (thermoplastic resin) Thermoplastic resin 1: Polyether ether ketone "Vestakeep 1000G" (manufactured by Daicel-Evonik, melting point 343°C, melt viscosity: 0.14 kPa·s (400°C), MFR: 158 g / 10 min (380°C), mass average molecular weight (Mw): 52000) (hereinafter referred to as "PEEK1") Thermoplastic resin 2: Polyether ether ketone "Vestakeep 4000G" (manufactured by Daicel-Evonik, melting point: 343°C, melt viscosity: 0.26 kPa·s (400°C), MFR: 13 g / 10 min (380°C), mass average molecular weight (Mw): 96,000) (hereinafter referred to as "PEEK2") Thermoplastic resin 3: Polyetherimide resin "Ultem 1000" (Sabic: glass transition temperature 217°C, non-crystalline, melt viscosity: 0.33 kPa·s (400°C), MFR: 25g / 10min (380°C), mass average molecular weight (Mw): 61000) Thermoplastic resin 4: Polybutylene terephthalate resin "Novaduran 5010R" (manufactured by Mitsubishi Engineering Plastics Corporation, melting point 224°C, melt viscosity: 0.12 kPa·s (300°C), MFR: 16 g / 10 min (MVR(cm 3 / 10 min) converted value at 250℃ 2.16 kg), mass average molecular weight: 88000

[0092] The melt viscosity of each resin is measured at a shear rate of 1000 s in accordance with ASTM D3835. -1 The melt viscosity at a temperature of 400°C is shown in Fig. 1. The melt viscosity of homopolybutylene terephthalate is measured at a shear rate of 1000 s -1 is the melt viscosity at a temperature of 300° C. Furthermore, the MFR of Thermoplastic Resins 1 to 3 is a value measured at 380° C. in accordance with JIS K7210 (2014). These thermoplastic resins were used as single resin compositions or blend compositions as shown in Table 1.

[0093] (thermosetting resin) Thermosetting resin 1: Bisphenol F type solid epoxy resin (Mitsubishi Chemical Corporation, polystyrene equivalent weight average molecular weight (Mw): 60,000) Thermosetting resin 2: Multifunctional epoxy resin with a structure containing four or more glycidyl groups per molecule (manufactured by Nagase ChemteX Corporation) Thermosetting resin 3: Hydrogenated bisphenol A type liquid epoxy resin (manufactured by Mitsubishi Chemical Corporation) Thermosetting resin 4: p-aminophenol type liquid epoxy resin (Mitsubishi Chemical Corporation)

[0094] Hardener: Phenolic resin hardener "MEH-8000H" (manufactured by Meiwa Kasei Co., Ltd.) Curing catalyst 1: 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-17')]-ethyl-s-triazine ("2E4MZ-A", manufactured by Shikoku Kasei Co., Ltd., a compound having a triazine ring as a heterocyclic structure containing a nitrogen atom. Molecular weight: 247)

[0095] (Thermal conductive filler) Thermally conductive filler 1: Plate-shaped boron nitride primary particles "AP-10S" (manufactured by MARUKA, average particle size (D50) 3.0 μm, specific surface area 10 m 2 / g). Thermally conductive filler 2: Agglomerated particles (secondary particles) of a so-called "cabbage" structure, formed by aggregating flat-plate-shaped boron nitride particles (primary particles) into a spherical shape. "PTX25" (manufactured by Momentive, average particle diameter (D50) 25 μm, specific surface area 7 m2 / g). Thermally conductive filler 3: boron nitride agglomerated particles having a house-of-cards structure produced according to WO 2015 / 119198 (average particle size (D50) 35 μm, maximum particle size (Dmax) 90 μm).

[0096] [Preparation of thermally conductive resin sheets of Examples 1 to 6 and Comparative Examples 1 and 2] (Melt mixing of thermoplastic resin and thermally conductive filler) The thermally conductive resin sheets of Examples 1 to 6 and Comparative Examples 1 and 2 were produced by mixing the types and amounts of thermoplastic resin and thermally conductive filler shown in Table 1 in the following manner. The thermoplastic resin and the thermally conductive filler were kneaded at 380° C. for 5 minutes in a Labo Plastomill ("4C150", manufactured by Toyo Seiki Co., Ltd.) to obtain a molten mixture of the thermoplastic resin and the thermally conductive filler.

[0097] The above-mentioned 5 minutes means that the total amount of the compounded thermoplastic resin and thermally conductive filler was approximately 60 to 80 g, and from that, a small amount of the thermoplastic resin was first added to the Labo Plastomill. After confirming that it was plasticized, a similar small amount of the thermally conductive filler was added, and this procedure was repeated until the entire compounded amount of approximately 60 to 80 g had been added, after which melt-kneading was carried out for a further 5 minutes. The amount of compound to be added is determined based on the bulk density of the compound and the internal volume of the Labo Plasto Mill (approximately 37.5 cm 3 ) was adjusted appropriately so that the amounts were approximately equal.

[0098] (Press molding of melt-kneaded material into sheets) Using a high-temperature vacuum press device (manufactured by Kitagawa Seiki Co., Ltd.), the molten and kneaded material was pressed for 10 minutes at a press temperature of 395°C and a press surface pressure of 10 MPa to obtain a thermally conductive resin sheet that was 15 cm square and 150 μm thick, and a thermally conductive resin sheet that was 15 cm square and 500 μm thick.

[0099] Here, the above-mentioned 10 minutes means that the inside of the vacuum press was preheated to 150°C, the molten kneaded material was put therein as a press-loaded composition, a light pressure of several MPa was applied to the molten kneaded material while operating the vacuum pump, the temperature inside the press was set to 395°C, and after 40 minutes of heating, the press surface pressure was set to 10 MPa, and pressing was performed for 10 minutes. After 10 minutes had elapsed, the temperature inside the press was again raised to 150° C., and when the internal temperature approached 150° C., the vacuum was released and the thermally conductive resin sheet was removed.

[0100] The press-prepared structure is a structure necessary for one batch press, in which a frame-shaped spacer 6 mm thick, with outer edges 20 cm long and wide, and with an internal opening of 15 cm x 15 cm long and wide is placed on the lower plated plate, the lump-to-powder mixture obtained by melt-kneading using the Labo Plastomill is scattered into the spacer in an amount of mass necessary to obtain a press sheet of 150 μm or 500 μm in thickness, and a drop lid 14.6 cm long and wide and 5.85 mm thick (when a sample of 150 μm in thickness is taken) or 5.50 mm thick (when a sample of 500 μm in thickness is taken) is fitted into the 15 cm x 15 cm opening, and the upper plated plate is placed on top.

[0101] However, in Comparative Example 1, since the homopolybutylene terephthalate resin "Novaduran 5010R" having a melting point of 224°C was used as the thermoplastic resin, the melt mixing temperature in the Labo Plastomill was set to 290°C, and the press molding temperature was set to 300°C, and thermally conductive resin sheets with thicknesses of 150 μm and 500 μm were obtained.

[0102] [Preparation of thermally conductive resin sheets of Comparative Examples 3 and 4] For Comparative Examples 3 and 4 in which an epoxy resin, which is a thermosetting resin, was used instead of a thermoplastic resin as the resin component, a thermally conductive resin sheet was produced as follows.

[0103] To each of the resin compositions shown in Table 2, 71.5% by mass of thermally conductive filler 3 was added to prepare a mixture such that the total amount of the resin component and the thermally conductive filler was 100% by mass. From there, 37.2% by mass of a mixed solution of MEK and cyclohexanone (mixing ratio (volume ratio) 1:1) was added and mixed so that the total solid concentration of the resin components and thermally conductive filler was 62.8% by mass. When mixing these, after manual mixing, stirring was performed for 2 minutes using a planetary stirrer "Awatori Rentaro" AR-250.

[0104] The coating slurry obtained above was applied onto a 38 μm-thick polyethylene terephthalate film (hereinafter referred to as "PET film") by the doctor blade method, and after heating and drying at 60°C for 120 minutes, it was pressed at a press temperature of 42°C and a press surface pressure of 15 MPa for 10 minutes to obtain an epoxy resin sheet-shaped molded product that was uncured or had only slightly progressed in the curing reaction. Thermally conductive resin sheets with thicknesses of 150 μm and 500 μm were obtained and used as test specimens.

[0105] <Measurement conditions and evaluation methods> The thermally conductive resin sheets of Examples 1 to 6 and Comparative Examples 1 to 4 were measured and evaluated by the following methods.

[0106] [Tensile storage modulus of resin component at 200℃ (E'(200))] A resin sheet having a thickness of 500 μm was prepared in the same manner as in each of the Examples, Comparative Examples, and Reference Examples except that no thermally conductive filler was added, and cut into a size of 4 mm×80 mm to prepare a test piece. Using a viscoelasticity spectrometer (product name "DVA-200", manufactured by IT Measurement Co., Ltd.), dynamic viscoelasticity was measured in the measurement temperature range of -100°C to 250°C under conditions of a vibration frequency of 10 Hz, a strain of 0.1%, a heating rate of 3°C / min, and a chuck distance of 1 cm, and the storage modulus (E'(200)) at a temperature of 200°C was read.

[0107] [Tensile storage modulus of resin component at 300℃ (E'(300))] A test piece was prepared in the same manner as in the measurement of E'(200) above, and the dynamic viscoelasticity was measured using a viscoelasticity spectrometer (product name "DVA-200", manufactured by IT Measurement Co., Ltd.) at a temperature range of -100°C to 350°C under the conditions of a vibration frequency of 10 Hz, a strain of 0.1%, a heating rate of 3°C / min, and a chuck distance of 1 cm, and the storage modulus at a temperature of 300°C (E'(300)) was read. The thermally conductive resin sheet of Comparative Example 1 was in a molten state and the tensile storage modulus at 300° C. could not be measured, so it was marked as "measurable." The thermal conductive resin sheets of Comparative Examples 3 and 4 were not measured, and therefore were marked with "-". The thermal conductive resin sheets of Comparative Examples 3 and 4 had a tensile storage modulus (E'(200)) at 200°C of already 4.0 x 10 7 Pa, the tensile storage modulus (E'(300)) at 300°C is also 4.0×10 7 It is expected to be below Pa.

[0108] [Mass gain at 85℃ / 85%RH] The thermally conductive resin sheets having a thickness of 500 μm produced in each of the Examples, Comparative Examples, and Reference Examples were cut into 8 cm×8 cm test pieces. First, each test piece was dried at 150°C for 1 hour, and the dry mass a (g) of the test piece was measured. Next, each test piece was stored in an environment of 85°C and 85% RH using a thermo-hygrostat "SH-221" (manufactured by Espec Corporation), and weighed every 24 hours to measure the mass (constant weight) b (g) at which the mass no longer changed. From the dry mass a (g) and mass (constant weight) b (g) obtained above, the mass increase rate was calculated using the following formula. Mass increase rate (%) = {(ba) / a} x 100

[0109] [Breakdown voltage after moisture absorption reflow test (BDV)] (Making a heat dissipation circuit board) The 150 μm thick thermally conductive resin sheet produced in each Example and Comparative Example was cut to a size of 40 mm × 80 mm, and one side of each of the 2000 μm thick copper plate with a size of 40 mm × 80 mm to be the metal plate material for heat dissipation and the 500 μm thick copper plate with a size of 40 mm × 80 mm to be the copper plate for forming the conductive circuit was polished in advance with #100 sandpaper to roughen the surface. The thermally conductive resin sheet was sandwiched so that the roughened surface of each of the copper plates of different thicknesses faced the thermally conductive resin sheet, and pressed to obtain a laminated heat dissipation sheet consisting of "metal plate material for heat dissipation (copper plate) / thermally conductive resin sheet / copper plate for forming the conductive circuit". The pressing conditions were as follows: for Examples 1 to 4, a pressing temperature of 390°C and a pressing pressure of 13 MPa for 10 minutes; for Examples 5, 6 and Comparative Example 2, a pressing temperature of 370°C and a pressing pressure of 13 MPa for 10 minutes; and for Comparative Example 1, a pressing temperature of 300°C and a pressing pressure of 13 MPa for 10 minutes.

[0110] In addition, for Comparative Examples 3 and 4, which are thermally conductive resin sheets made of thermosetting resin, a 150 μm thick epoxy resin sheet that was uncured or in which the curing reaction had only progressed very slightly was pressed for 30 minutes at a press temperature of 175° C. and a press surface pressure of 10 MPa to complete the curing reaction of the thermosetting resin, thereby obtaining a laminated heat dissipation sheet consisting of "heat dissipating metal plate material (copper plate) / thermally conductive resin sheet / copper plate for forming conductive circuit."

[0111] The copper plate for forming the conductive circuit of each of the laminated heat dissipation sheets was then etched and patterned by a predetermined method to obtain a heat dissipation circuit board. The pattern was such that two copper plates for the conductive circuit with a circular pattern of φ25 mm remained on a thermally conductive resin sheet of 40 mm × 80 mm.

[0112] (Measurement of dielectric breakdown voltage (BDV)) The heat dissipating circuit boards of each Example and Comparative Example were stored in an environment of 85°C and 85%RH for 3 days using a thermohygrostat SH-221 (manufactured by Espec Corporation), and then heated from room temperature to 290°C in 12 minutes in a nitrogen atmosphere within 30 minutes, held at 290°C for 10 minutes, and then cooled to room temperature (moisture absorption reflow test). Thereafter, the heat dissipating circuit board was immersed in Fluorinert FC-40 (manufactured by 3M Corporation), and an ultra-high voltage withstand voltage tester 7470 (manufactured by Keisoku Gijutsu Kenkyusho Co., Ltd.) was used to place a φ25mm electrode on a φ25mm copper plate patterned by etching on the heat dissipating circuit board, apply a voltage of 0.5kV, and increase the voltage by 0.5kV every 60 seconds, and measurements were performed until dielectric breakdown occurred. The measurements were performed at a frequency of 60Hz and a voltage increase rate of 1000V / sec.

[0113] When the breakdown voltage per unit thickness (converted value for a thickness of 1 mm) was 60 kV / mm or more, it was marked as "Good", when it was 40 kV / mm or more but less than 60 kV / mm, it was marked as "Good", and when it was less than 40 kV / mm, it was marked as "Poor". The measurement results are shown in Tables 1 and 2. The evaluation of the dielectric breakdown voltage (BDV) after the moisture absorption reflow test can be used as an evaluation of the moisture absorption reflow resistance.

[0114] [Interface observation after moisture absorption reflow test] After the heat dissipation circuit boards of each Example and Comparative Example were subjected to a moisture absorption reflow test in the same manner as above, the interface between the copper electrode of φ25 mm patterned by the above etching and the thermally conductive resin sheet was observed using an ultrasonic imaging device FinSAT (FS300III) (manufactured by Hitachi Power Solutions). The measurement was performed by placing the sample in water using a probe with a frequency of 50 MHz, a gain of 30 dB, and a pitch of 0.2 mm.

[0115] The evaluation results are shown in Tables 1 and 2. The evaluation of the interface observation after the moisture absorption reflow test can be made as to whether or not interfacial peeling due to thermal expansion and thermal contraction and deformation due to foaming of the thermal conductive resin sheet are likely to occur when the thermal conductive resin sheet is laminated with a metal plate and subjected to a reflow process.

[0116] [Thermal conductivity at 25℃] From the thermally conductive resin sheets with a thickness of 500 μm prepared in each Example and Comparative Example, a measurement sample was cut into a size of 10 mm square. After a thin layer of laser light absorbing spray (Fine Chemical Japan's "Black Guard Spray FC-153") was applied to both sides and dried, the thermal diffusivity a (mm 2 The measurement was carried out on five points cut out from the same sheet, and the arithmetic average value was calculated.

[0117] In addition, the density ρ (g / m) of the resin sheet was measured using a specific gravity measuring instrument (manufactured by A&D Co., Ltd.). 3 ) was obtained, and the specific heat capacity c (J / (g K)) at 25 °C was measured using a DSC measuring device (ThermoPlusEvo DSC8230, Rigaku Corporation). From these measured values, the thermal conductivity (W / m k) in the sheet thickness direction at 25°C was calculated as "H = a × ρ × c".

[0118] The thermal diffusivity a (mm 2 Since there is no JIS standard for the thermal diffusivity and thermal conductivity of resin-based materials, JIS R1611-2010 (Method of measuring thermal diffusivity, specific heat capacity, and thermal conductivity of fine ceramics by flash method) was used as a reference. Since the standard specifies that the thickness of the sample should be 0.5 mm or more and 5 mm or less, only the samples used for thermal conductivity measurement were measured at a thickness of 0.5 mm. Furthermore, density ρ is a value obtained by the Archimedes method in accordance with JIS K6268. Furthermore, specific heat capacity c is a value obtained by using a DSC measuring device in accordance with JIS K7123.

[0119] In addition, for the thermal conductivity measurement specimens of Comparative Examples 3 and 4 using thermosetting resins, a 500 μm-thick piece was taken from the sheet-shaped molded body, which was then placed together with the PET film in a hot air oven at 170° C. for 1 hour to harden the sheet-shaped molded body, and the PET film was peeled off to prepare the specimen.

[0120] [Table 1]

[0121] The thermally conductive resin sheets of Examples 1 to 6 have a tensile storage modulus (E'(200)) of the resin component at 200°C of 8.0 × 10 7 Pa or more 1.0×10 10 The resin composition had a mass increase rate of 0.15% or less at 85°C and 85% RH, and had good moisture absorption reflow resistance. These thermally conductive resin sheets had a tensile storage modulus (E'(300)) of the resin component at 300°C of 4.0×10 7 Pa or more 1.0×10 9 The pressure was below 1 Pa. On the other hand, the thermally conductive resin sheets of Comparative Examples 1 to 4, which had tensile storage moduli (E'(200), E'(300)) or mass increase rates outside the above ranges, had a breakdown voltage of less than 40 kV / mm after the moisture absorption reflow test, and had reduced voltage resistance. In particular, in Comparative Examples 3 and 4, not only was the breakdown voltage after the moisture absorption reflow test low, but peeling or lifting and relatively significant void generation were also observed at the interface between the thermally conductive resin sheet and the copper electrode. From the above, the thermally conductive resin sheet of the present invention has a tensile storage modulus (E') of the resin component at 200°C of 8.0 × 10 7 Pa or more 1.0×10 10 Pa or less, and the mass increase rate of the resin composition at 85°C and 85% RH is 0.15% or less, or the tensile storage modulus (E'(300)) of the resin component at 300°C is 4.0 x 10 7 Pa or more 1.0×10 9It has been found that by having a mass increase rate of the resin composition of 0.15% or less at 85°C and 85% RH, the moisture absorption reflow resistance is better than that of thermally conductive resin sheets using conventional thermosetting resins such as epoxy-based resins, while using a thermoplastic resin with good moldability and processability.

[0122] Furthermore, from Examples 1 to 3, it was found that when boron nitride is used as a thermally conductive filler, the thermal conductivity is higher when boron nitride agglomerated particles are used than when flat boron nitride primary particles are used, and in particular, the thermal conductivity is higher when card-house structured boron nitride agglomerated particles are used than when cabbage-structured boron nitride agglomerated particles are used.

[0123] Examples 5 and 6 use a blend of PEEK, a crystalline thermoplastic resin having a melting point of 300°C or higher, and PEI, a non-crystalline thermoplastic resin. Examples 3, 5, and 6 show that blending PEI, which has a high glass transition temperature, can increase the tensile storage modulus (E'(200)) of the resin component at 200°C. In Examples 5 and 6, the glass transition temperature of the blended PEI is 217°C, so the tensile storage modulus (E'(300)) of the resin component at 300°C is lower than in Example 3, but the E'(300) is 4.0×10 7 Since the tensile strength was 1.0 Pa or more, there was no effect on the moisture absorption reflow resistance. In addition, although the mass increase rate of Examples 5 and 6 was increased compared to Example 3 by blending PEI, it was found that there was no effect on the moisture absorption reflow resistance as long as the mass increase rate was 0.15% or less. From the above, it has been found that the thermally conductive resin sheet of the present invention preferably contains a crystalline thermoplastic resin as a main component having a melting point of 300° C. or higher.

Claims

1. A resin composition comprising a thermoplastic resin and a thermally conductive filler, the thermoplastic resin is a blended resin of polyether ether ketone and another thermoplastic resin, and the melting point of the blended resin is 300° C. or higher; the thermally conductive filler comprises agglomerated particles of boron nitride; The tensile storage modulus (E'(300)) of the thermoplastic resin at 300°C is 4.0 x 10 7 Pa or more, 2.0×10 8 Pa or less, The resin composition has a mass increase rate of 0.15% or less at 85° C. and 85% RH.

2. A resin composition comprising a thermoplastic resin and a thermally conductive filler, The thermoplastic resin includes polyetheretherketone and polyetherimide, the thermally conductive filler comprises agglomerated particles of boron nitride; The tensile storage modulus (E'(300)) of the thermoplastic resin at 300°C is 4.0 x 10 7 Pa or more, 2.0×10 8 Pa or less, The resin composition has a mass increase rate of 0.15% or less at 85° C. and 85% RH.

3. The resin composition according to claim 2 , wherein a content ratio of the polyetherimide is 50% by mass or less with respect to 100% by mass of the thermoplastic resin.

4. The tensile storage modulus (E'(200)) of the thermoplastic resin at 200°C is 8.0 x 10 7 Pa or more, 1.0×10 10 The resin composition according to any one of claims 1 to 3, wherein the viscosity is 100 Pa or less.

5. The resin composition according to any one of claims 1 to 4, wherein the thermoplastic resin is contained in an amount of 15% by mass or more and 40% by mass or less, and the thermally conductive filler is contained in an amount of 60% by mass or more and 85% by mass or less, in 100% by mass of the resin composition.

6. The resin composition according to any one of claims 1 to 5, wherein the boron nitride contained in the thermally conductive filler is composed of spherical boron nitride particles and flat boron nitride particles, and the volume ratio of the spherical boron nitride particles to the total amount of the boron nitride is 75 volume% to 99 volume%, except for those in which the volume ratio of the spherical boron nitride particles to the total amount of the boron nitride is 75 volume% to 99 volume%.

7. The resin composition according to any one of claims 1 to 6, wherein the boron nitride agglomerated particles have a house of cards structure.

8. A thermally conductive resin sheet comprising the resin composition according to any one of claims 1 to 7.

9. The thermally conductive resin sheet according to claim 8, having a thickness of 50 μm or more and 300 μm or less.

10. The thermally conductive resin sheet according to claim 8 or 9, having a thermal conductivity in the thickness direction at 25°C of 5.0 W / m·K or more.

11. The thermal conductive resin sheet according to any one of claims 8 to 10, wherein the breakdown voltage (BDV) after a moisture absorption reflow test measured by the following method for a heat dissipation circuit board manufactured by the following method is 60 kV / mm or more per unit thickness. <Method of manufacturing heat dissipation circuit board> A thermally conductive resin sheet having a thickness of 150 μm is cut to a size of 40 mm × 80 mm, and one side of each of a 2000 μm thick copper plate having a size of 40 mm × 80 mm as a metal plate material for heat dissipation and a 500 μm thick copper plate having a size of 40 mm × 80 mm as a copper plate for forming a conductive circuit is polished in advance with #100 sandpaper to roughen the surface, and the thermally conductive resin sheet is sandwiched so that the roughened surface of each copper plate faces the thermally conductive resin sheet, and pressed at a press temperature of 390 ° C. and a press surface pressure of 13 MPa for 10 minutes to obtain a laminated heat dissipation sheet consisting of a metal material for heat dissipation (copper plate) / a thermally conductive resin sheet / a copper plate for forming a conductive circuit. The copper plate for forming the conductive circuit is further etched and patterned to obtain a heat dissipation circuit board. At this time, the pattern is made so that two copper plates for forming conductive circuits with a circular pattern of φ25 mm remain on a thermally conductive resin sheet of 40 mm×80 mm. <Method for measuring BDV after moisture absorption reflow test> A heat dissipative circuit board is stored in an environment of 85°C and 85% RH for 3 days using a thermo-hygrostat, and then within 30 minutes, the temperature is raised from room temperature to 290°C in 12 minutes under a nitrogen atmosphere, and the board is held at 290°C for 10 minutes and then cooled to room temperature (moisture absorption reflow test). The heat dissipating circuit board after the moisture absorption reflow test is immersed in a fluorine-based inert liquid, and a φ25 mm electrode is placed on a φ25 mm copper plate patterned by etching on the heat dissipating circuit board using an ultra-high voltage withstand voltage tester, and a voltage of 0.5 kV is applied, and the voltage is increased by 0.5 kV every 60 seconds, and measurements are taken until dielectric breakdown occurs. The measurements are taken at a frequency of 60 Hz and a voltage increase rate of 1000 V / sec.

12. A laminated heat dissipation sheet comprising the thermally conductive resin sheet according to any one of claims 8 to 11 and a heat dissipation metal material laminated on one surface of the sheet.

13. A heat dissipating circuit board comprising the laminated heat dissipating sheet according to claim 12.

14. 14. The heat dissipation circuit board according to claim 13, further comprising a conductive circuit laminated on the other surface of the thermally conductive resin sheet.

15. A power semiconductor device comprising the heat dissipation circuit board according to claim 13 or 14.

Citation Information

Patent Citations

  • Film for metallic substrate

    JP1991020354A

  • Composite material resistant to high temperature

    JP1991126765A

  • Compatible resin composition

    JP1991207754A

  • Heat-resistant and heat conductive packing

    JP1995157569A

  • Printed wiring board film and printed wiring board

    JP2003026914A